A Critical Research on Bryson’s Strategic Management Model - Yaghoob Maharati; Fatemeh Beygi Nasrabadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Theory analysis and critique is the first step in a thorough and in-depth understanding of the theory and the entry into the theorizing in a particular field. This study aims to emphasize the extension of criticism culture in the organization and management literature. In this article, Bryson’s strategic planning theory select for the critic as a sample of theory criticism. Since Bryson's strategic planning model is one of the most well-known studies in the field of strategic planning in the world and a large number of research and practices have used this model. This study used a combined criticism method to analyze and critic this theory, based on content, methodology, historical point of view, and also the personal and professional life of the theorist. The results discuss the strengths and weaknesses of the theory, especially in terms of content and methodology, and explain the impact of the theoretical, intellectual, social, and historical context of the theory and discuss the application of the theory in Iranian organizations.